Método para reconstrucción de escenas sin ´línea de visión basado en una representación neuronal - Rodriguez-Sanz, Salvador; Gutiérrez Pérez, Diego; Redo-Sanchez, Albert (Jornada de Jóvenes Investigadores del I3A, 2024)
Non-Line-of-Sight Imaging (NLOS) addresses the challenge of capturing a scene which is not directly visible from a sensor line-of-sight, obscured by an occluder. This work uses time-of-flight formulation to propose a learning-based method that represents implicitly the hidden scene partially disambiguated by transient imaging and explores new visibility features coherent with this representation.